Experimental results on fluctuations of conserved charges confronted with predictions from canonical thermodynamics - Braun-Munzinger, Peter; Rustamov, Anar; Stachel, Johanna (Nuclear physics. A, Nuclear and hadronic physics, 2019)
The study of multiplicity distributions of identified particles in terms of their higher moments is at the focus of contemporary experimental and theoretical studies. In a thermalized system combinations of these moments are directly related to the Equation of State (EoS) through variations of the thermodynamic pressure with respect to changes in the chemical potential μQ, associated with a conserved charge Q. The ultimate goal of the experimental measurements in relativistic nuclear collisions is, by systematics comparison to the ab initio theoretical calculations, to probe the dynamics of genuine phase transitions between a hadron gas and the quark-gluon plasma. However, the comparison between experiment and theory is far from trivial, because several non-dynamical fluctuations need to be controlled prior to a meaningful comparison to theoretical predictions. In this report we present quantitative estimates for these non-dynamical contributions using the Canonical Ensemble (CE) formulation of the statistical mechanics. Together with the analytical formulas we provide also results from Monte Carlo simulations within the CE and compare our predictions with the corresponding measurements from the STAR experiment.
Gesehen am 21.10.2019